Child abuse syndrome – a forensic case of fatal impulsive act of violence - Tsranchev, Ivan; Timonov, Pavel; Spasov, Svetlozar; Dobrev, Todor; Yancheva, Stela; Gulinac, Milena; Fasova, Antoaneta (Folia Medica, 2022)
Child abuse syndrome is a medico-social problem widely spread around the world, which includes a complex of clinically manifested forms of violence against children. This syndrome includes different forms of physical violence, sexual violence, neglect, and emotional violence against children. The main problem with this type of violence continues to be the large number of unregistered “hidden” cases. The consequences of violence against children are serious and have a lasting negative effect on the physical and mental health of the victims. Child abuse is often a result of impulsive violent behavior with minimal provocation and may have a fatal outcome. We present a case of a 3-year-old boy, admitted to the Emergency Department of the Municipal Hospital in Asenovgrad, Bulgaria, in a state of biological death. Case circumstances during the police investigation were unclear and the body was transported for forensic examination. During the forensic autopsy, many traumatic injuries were observed over the whole body – bruises of different ages, fractures of bones, abdominal trauma with bucket-handle tear of the mesentery, thoracic trauma with contusions and ruptures of the lungs, rupture of the diaphragm, and many other injuries that are specific predictors for this type of child physical abuse. The main aim of the present report is to enrich the knowledge of medical workers in their routine practical work in the identification and determination of child abuse syndrome. It could prevent the fatal outcome and reduce the mortality from this specific type of violence.